UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI OPERASI HITUNG CAMPURAN BILANGAN BULAT DENGAN MENGGUNAKAN METODE SIMULASI ROLE PLAYING - Lestari, Dirga Ayu (Fakultas Agama Islam, Universitas Mathla'ul Anwar, 2022)
The objectives to be achieved from this Classroom Action Research are: 1) To improve the learning outcomes of fifth grade students at SDN Sukacai 2 in learning mathematics on the subject of mixed integer arithmetic operations. 2) To increase the learning activities of fifth grade students at SDN Sukacai 2 in learning mathematics with mixed integer arithmetic operations using the role playing simulation method. The form of the research used was collaborative research with the Classroom Action Research (PTK) model which consisted of two cycles and each cycle consisted of planning, action, observation, and reflection. Processing and analysis of data obtained by means of a test, which is a technique to confirm findings during learning takes place, and the results are discussed with the school to obtain responses to the findings before drawing conclusions. The conclusions obtained indicate an improvement in student learning outcomes. This is indicated by the value of student activity starting from cycle I with a value of 1.75 and cycle II obtaining a value of 3.08, while student learning outcomes starting from pre-cycle 33.82 experience an increase in cycle I to 60.00, and in cycle II it increases to 88.00. In fact, the percentage of student learning completeness increased from 5.45% (pre-cycle) to 43.64% (cycle I), and increased to 90.91% (cycle II).